Topical Loperamide-Encapsulated Liposomal Gel Increases the Severity of Inflammation and Accelerates Disease Progression in the Adjuvant-Induced Model of Experimental Rheumatoid Arthritis - Hua, Susan; Dias, Thilani H.; Pepperall, Debbie-Gai; Yang, Yuan (Frontiers in Pharmacology, 2017)
This study evaluates the prophylactic effect of the peripherally-selective mu-opioid receptor agonist, loperamide, administered topically in a liposomal gel formulation on pain, inflammation and disease progression in the adjuvant-induced model of experimental rheumatoid arthritis in female Lewis rats. In a randomized, blinded and controlled animal trial, AIA rats were divided into six groups consisting of eleven rats per group based on the following treatments: loperamide liposomal gel, free loperamide gel, empty liposomal gel, diclofenac gel (Voltaren®), no treatment, and naive control. Topical formulations were applied daily for a maximum of 17 days – starting from day 0 at the same time as immunization. The time course of the effect of the treatments on antinocieption and inflammation was assessed using a paw pressure analgesiometer and plethysmometer, respectively. Arthritis progression was scored daily using an established scoring protocol. At the end of the study, hind paws were processed for histological analysis. Administration of loperamide liposomal gel daily across the duration of the study produced significant peripheral antinociception as expected; however, increased the severity of inflammation and accelerated arthritis progression. This was indicated by an increase in paw volume, behavioral and observational scoring, and histological analysis compared to the control groups. In particular, histology results showed an increase in pannus formation and synovial inflammation, as well as an upregulation of markers of inflammation and angiogenesis. These findings may have implications for the use of loperamide and other opioids in arthritis and potentially other chronic inflammatory diseases.